Design of an object-oriented framework for modelling the partitioning of captured solar radiation and evapotranspiration in intercropping systems - Teh, Christopher Boon Sung; Wheeler, T. R. (Universiti Putra Malaysia Press, 2012)
x-library is a C++ object-oriented framework for modelling the partitioning of captured solar radiation and evapotranspiration in intercropping systems. The design and analysis of the x-library are done to ensure that the soil-plant-atmosphere system is categorised into classes, such as weather, microclimate, intercrop, crop, canopy, leaf, roots, soil, heat, and radiation. Meanwhile, x-library implements two kinds of solar radiation models; namely, one-dimensional (1-D), and two-dimensional (2-D) model, where irradiance varies in one dimension (vertical) and in two dimensions (vertical and horizontal), respectively. Radiation partitioning is based on weighting criteria so that a crop having the larger leaf area index and extinction coefficient would have greater share of captured radiation. Evapotranspiration partitioning is calculated using the Shuttleworth- Wallace equation. Model comparisons with a field experiment showed an overall good agreement between the simulated and measured solar radiation and transpiration values. A graphical user interface front-end for the x-library known as the x-model was also developed, primarily for non-modellers and non-programmers.